Efficacy of Dietary Treatment for Inducing Disease Remission in Eosinophilic Gastroenteritis. (July 2015) - Lucendo, Alfredo J.; Serrano-Montalbán, Beatriz; Arias, Ángel; Redondo, Olga; Tenias, José M.
ABSTRACT: Objectives: Various dietary interventions have been used to treat patients with eosinophilic gastroenteritis (EGE). Concrete evidence as to the effectiveness of such treatments in inducing disease remission is, however, lacking. The aim of the study was to systematically review the efficacy of dietary therapies in inducing EGE remission. Methods: We performed a systematic search for the MEDLINE, EMBASE, and SCOPUS libraries for studies investigating the efficacy of dietary interventions (in both histological and symptomatic remission) for children and adults with EGE and colitis. Results: The search yielded 490 references; 30 were included in the review, with most of these references being "low-quality" individual cases or short case series. No significant publication bias was found. Elemental diets in children were linked to 75.8% of clinical improvement, but few of these patients underwent a histological evaluation. Allergy-testing results have been used scarcely in EGE. Empiric elimination of allergy-associated foods was the most commonly used option. The variable results in terms of symptom relief, however, were scarcely accompanied by histological confirmation. Clinical and methodological heterogeneity hindered the performance of quantitative summaries for the efficacy of dietary therapies in inducing disease remission. Conclusions: Symptomatic improvements reported for dietary treatment in EGE by most of the available literature are questionable because of the lack of objective evaluation of clinical changes and the very limited assessment of histological remission. Because of the relative lack of well-designed, high-quality studies, the unequivocal use of dietary treatment for patients with EGE and colitis cannot be supported. Further research should be undertaken.